Effect of soybean yellow mottle mosaic virus (Gammacarmovirus glycinis) on growth, yield and seed quality of soybean (Glycine max) cultivars - M, SRIKANT; SANDRA, NAGAMANI; LAL, SANJAY KUMAR (The Indian Journal of Agricultural Sciences, 2025)
Gammacarmovirus glycinis [Soybean yellow mottle mosaic virus, (SYMMV)] is an important viral pathogen associated with mosaic and mottle symptoms in leguminous crops including soybean (Glycine max L.). The present study was carried out during the year 2022 at ICAR-Indian Agricultural Research Institute, New Delhi to understand the impact of SYMMV on various growth, seed yield and quality parameters in 18 soybean (Glycine max L.) cultivars through mechanical sap inoculation under controlled environmental conditions. SYMMV infection significantly influenced the plant height, number of pods and seed yield/plant, 100-seed weight, germination%, seedling length, seedling fresh weight and dry weight, seedling vigour index-I and II across all cultivars. Cultivars like SL-688 and SL-744 exhibited notable reduction in plant height whereas number of pods and seed yield/plant was recorded low in SL-744, SL-958, SL-1104 and JS-335. Great variation in 100-seed weight was observed for the cultivars MACS-450 and MACS 1281 compared to other cultivars. Seed germination was significantly reduced in cultivars SL-688 and SL-744 whereas seedling length was greatly influenced in the cultivars SL-744, JS-335, DSB-23 and MACS-57. Both seedling vigour index I and II were negatively affected particularly in Sl-525, SL-688, SL-744, DSB-23, and JS-335. The soybean cultivars SL-525, SL-688, SL-744, SL-958, SL-1104, JS-335, DSB-23, MACS-57 and MACS-1281 exhibited the great reduction in growth and seed quality parameters confirming their high susceptibility to SYMMV infection. The study highlights that while all cultivars experienced some negative effects, the degree of impact varied significantly. The findings of this study points to the importance of monitoring and managing SYMMV infection in soybean crop to prevent significant agricultural losses and maintain seed quality and crop productivity.